Enhanced pathogenicity and neurotropism of mouse-adapted H10N7 influenza virus are mediated by novel PB2 and NA mutations - Zhang, Xuxiao; Xu, Guanlong; Wang, Chenxi; Jiang, Ming; Gao, Weihua; Wang, Mingyang; Sun, Honglei; Sun, Yipeng; Chang, Kin-Chow; Liu, Jinhua; Pu, Juan (Microbiology Society, 2017)
The H10 subtype of avian influenza viruses (AIVs) circulates globally in wild birds and poultry, and this subtype has been shown to be increasingly prevalent in China. Among the various H10 viruses, H10N7 AIVs have caused repeated mammal and human infections. To investigate their genetic adaptation in mammals, we generated a mouse-adapted avian H10N7 variant (A/mallard/Beijing/27/2011-MA; BJ27-MA) which exhibited increased virulence in mice compared to wild-type virus and acquired neurotropism. Sequencing showed the absence of the widely recognized mammalian adaptation markers of E627K and D701N in PB2 in the mouse-adapted strain; instead, five amino acid mutations were identified: E158G and M631L in PB2; G218E in haemagglutinin (H3 numbering); and K110E and S453I in neuraminidase (NA). The neurovirulence of the BJ27-MA virus necessitated the combined presence of the PB2 and NA mutations. Mutations M631L and E158G of PB2 and K110E of NA were required to mediate increased virus replication and severity of infection in mice and mammalian cells. PB2-M631L was functionally the most dominant mutation in that it strongly upregulated viral polymerase activity and played a critical role in the enhancement of virus replication and disease severity in mice. K110E mutation in NA, on the other hand, significantly promoted NA enzymatic activity. These results indicate that the novel mutations in PB2 and NA genes are critical for the adaptation of H10N7 AIV in mice, and they could serve as molecular signatures of virus transmission to mammalian hosts, including humans.